Peningkatan Hasil Belajar Materi Perkalian Dua Buah Bilangan Melalui Strategi Pembelajaran Aritmatika Jari Pada Siswa Kelas II SDN Buncitan Sedati Sidoarjo - Ngunisari Saptowati Handayani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the students tend to be passive in learning. Students understand difficult material multiplication of two numbers mathematics courses. Math is one subject that is not favored children. Focus question in this research is "How can improve learning outcomes matter multiplication of two numbers mathematics courses second grade students of SDN Buncitan Sidoarjo? The goal is to know the material improvement of learning outcomes multiplication of two numbers mathematics courses arithmetic finger strategy through second grade students of SDN Buncitan Sidoarjo. Arithmetic finger is one of the subjects of mathematics learning strategy that uses the fingers as a tool to improve understanding of the material multiplication of two numbers. To facilitate the teaching material in the multiplication of two numbers. As treasury for teaching learning strategies in the multiplication of two numbers.This study uses a quantitative approach. The data required in this study is testing and observation. The results obtained on the learning strategy arithmetic finger elementary mathematics courses can improve student learning outcomes, especially in the multiplication of two numbers